Sarcolemmal loss of active nNOS (Nos1) is an oxidative stress‐dependent, early event driving disuse atrophy. Issue 4 (24th October 2018) - Lechado i Terradas, Anna; Vitadello, Maurizio; Traini, Leonardo; Namuduri, Arvind Venkat; Gastaldello, Stefano; Gorza, Luisa
Abstract: Skeletal muscle atrophy following unloading or immobilization represents a major invalidating event in bedridden patients. Among mechanisms involved in atrophy development, a controversial role is played by neuronal NOS (nNOS; NOS1), whose dysregulation at the protein level and/or subcellular distribution also characterizes other neuromuscular disorders. This study aimed to investigate unloading‐induced changes in nNOS before any evidence of myofiber atrophy, using vastus lateralis biopsies obtained from young healthy subjects after a short bed‐rest and rat soleus muscles after exposure to short unloading periods. Our results showed that (1) changes in nNOS subcellular distribution using NADPH‐diaphorase histochemistry to detect enzyme activity were observed earlier than using immunofluorescence to visualize the protein; (2) loss of active nNOS from the physiological subsarcolemmal localization occurred before myofiber atrophy, i.e. in 8‐day bed‐rest biopsies and in 6 h‐unloaded rat soleus, and was accompanied by increased nNOS activity in the sarcoplasm; (3) nNOS ( Nos1 ) transcript and protein levels decreased significantly in the rat soleus after 6 h and 1 day unloading, respectively, to return to ambulatory levels after 4 and 7 days of unloading, respectively; (4) unloading‐induced nNOS redistribution appeared dependent on mitochondrial‐derived oxidant species, indirectly measured by tropomyosin disulfide bonds which had increased significantly in the rat soleus already after a 6 h‐unloading bout; (5) activity of displaced nNOS molecules is required for translocation of the FoxO3 transcription factor to myofiber nuclei. FoxO3 nuclear localization in rat soleus increased after 6 h unloading (about four‐fold the ambulatory level), whereas it did not when nNOS expression and activity were inhibited in vivo before and during 6 h unloading. In conclusion, this study demonstrates that the redistribution of active nNOS molecules from sarcolemma to sarcoplasm not only is ahead of the atrophy of unloaded myofibers, and is induced by increased production of mitochondrial superoxide anion, but also drives FoxO3 activation to initiate muscle atrophy. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.